Why follow-up examinations after left atrial appendage closure are important: detection of complications during follow-up and how to deal with them - Wunderlich, Nina C.; Lorch, Gabriele C.; Honold, Jörg; Franke, Jennifer; Küx, Harald (Current cardiology reports, 2020)
Device-related thrombus (DRT) formation and incomplete left atrial appendage closure (LAAC) are the two major complications that can occur after LAAC and can potentially limit the success of such a procedure. This review discusses the incidence, clinical and/or prognostic significance, detection methods, treatment options, and potential strategies to prevent these complications.
Gesehen am 24.09.2020